The Economic Value of Auditing and Its Effectiveness in Public School Operations - SAITO, YOSHIE; MCINTOSH, CHRISTOPHER S. (Contemporary Accounting Research, 2010)
We examine the impact of auditing on public school operations with two objectives: to investigate whether audits provide economic benefits to stakeholders and how complex compliance rules impact auditing effectiveness. Utilizing auditing time data and a unique opportunity presented by the Quality Basic Education Act in Georgia, we estimate the relative performance of school district operations employing a stochastic frontier estimation technique. We find that auditing produces real economic benefits for stakeholders by mitigating inefficiency in the use of school resources. We also find that stringent compliance rules reduce an audit’s effectiveness but auditors’ experience can help to overcome the problems. The lack of disclosure of auditing costs hinders the ability to conduct a cost–benefit analysis of new requirements. Our analysis supports the notion that auditing is vital to establish governance mechanisms and disclosure of auditing costs is important to adequately evaluate a new policy. Data are available from the public sources identified in the text.